Adolescent-to-adolescent development a pilot assessment of adolescent peer organised network - Khan, Md. Kaisar A; Nath, Samir Ranjan; Kabir, Md. Mahbubul (BRAC Research and Evaluation Division (RED), 2019)
This is an early assessment of BRAC's Adolescent Peer Organised Network (APON) programme - an initiative towards adolescent-to-adolescent development in order to acquire and share knowledge through peer organised network. This study aimed to examine the knowledge of the participants of this programme, measure changes in their attitude, know status of knowledge dissemination, whether leadership skills are developed, and know perception of the course participants and others. Data were collected from 200 adolescents from two areas (team offices) of two regions under BRAC Education Programme. A half of the sampled adolescents was programme participants and the rest non-participants. The selected adolescents were interviewed using structured questionnaire, which contained a test and related questions. Focus group discussions were also held with the programme participants and their mothers separately. Findings reveal that the APON course participants had significantly better knowledge than the non-participants in different social, legal, health and environmental issues. Their attitude on some issues was positively different than the non-participants. The course participants disseminated their knowledge to others, especially among the peer adolescents. The initiative developed leadership quality among the participants to some extent. The course is being accepted gradually in the society. This course would benefit the adolescents if they can implement their knowledge in real life situation, for instance, through linking this course with occupation and everyday life and continuing the network for longer period.